CILOSTAZOL DID NOT INDUCE ANY ADVERSE REACTIONS IN CORONARY ARTERIAL DISEASE (NON-ST ELEVATION MYOCARDIAL INFARCTION) WITH CONGESTIVE HEART FAILURE COMORBIDITY: A CASE REPORT - Sukmawan, Yedy Purwandi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The study to monitor the adverse reactions related to cilostazol used in coronary arterial disease with congestive heart failure comorbidity. This case report describes monitored 63-year-old males with dyspnea that had recently begun using cilostazol after switched from aspirin caused by asthma related to aspirin. After 10 days monitored for adverse reactions of cilostazol used, revealed there was no adverse reaction to be related to cilostazol and the patient came home with improvement. Cilostazol did not show any adverse reactions in this report. However, more data and longterm monitoring willneeded.In addition, biologic variations may influence. Therefore, need to determine which population do not affect the harm of cilostazol. Keywords: Dyspnea, Cilostazol, Monitoring.